Transforming Caste Traditions: Intracultural Communication and Structural Changes Among the Kei People in Southeast Maluku - Moh Yamin Rumra; Saidin Ernas; Muliadi Mau (SCAD Independent, 2026)
This study investigated the persistence and transformation of caste-based social stratification in Kei society, Southeast Maluku, amid processes of modernization and local democratization. While everyday social interactions increasingly reflected more fluid relations, traditional caste distinctions between Mel-mel, Ren-ren, and Iri-ri remained embedded in customary institutions, religious practices, and local political structures. This research aimed to examine how caste relationships were reproduced, negotiated, and contested through intracultural communication. Adopting a qualitative ethnographic design, data were collected through prolonged field observation, in-depth interviews with community members in caste groups, and analysis of customary practices, ritual roles, and local political participation. The findings showed that caste domination persisted through the sacralization of tradition, symbolic hierarchies, and patterns of economic dependence that normalized unequal social positions. At the same time, expanded access to education and participation in postreform local democratic processes enabled members of the Iri-ri group to renegotiate social identities and challenged inherited stigmas, particularly in political and bureaucratic arenas. This study demonstrated that caste in Kei society operated as a dynamic communicative process that simultaneously sustained social order and opened spaces for gradual transformation. The findings contribute to broader discussions on power, culture, and social inequality in post-traditional and indigenous societies.